The globalisation of the oceans : containerisation from the 1950s to the present - Broeze, Frank (Research in maritime history, 2019)
This book maintains that container shipping is vital to the actualisation of globalisation, and that without it, globalisation would remain a concept rather than reality. It argues that container shipping has been academically overlooked as a global business sector in favour of more prominent sectors such as oil or arms trade, and aims to provide a complete history of containerisation from the 1950s to the turn of the millennium. This history explores the growth of the container industry due to prominent innovation in vessel design, early adoption of the internet, large international mergers, and significant physical alterations to the global port system. With particular emphasis on the east-west trade, the chapters cover the growth and development of the container industry, to the social changes experienced by seafaring labour forces, the cultural impact of the container - bringing a domineering land-presence to maritime activity, through to the environmental concerns surrounding the industry. The study is not a quantitative economic analysis of the industry, rather, an updated history that strives to demonstrate the importance of transport infrastructures to any consideration of global business sectors, by providing evidence of the container industry's stimulation of the global economy.